2019
DOI: 10.1108/hff-11-2018-0693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MWCNT/ethylene glycol nanofluid flow in a parabolic trough collector with glass-glass absorber tube

Abstract: Purpose Because of its increased absorptance in fluid and reduced heat loss, direct absorption nanofluid (DANF) is receiving intense interest as an efficient way to harvest solar energy. This work aims to investigate, for the first time, the application of DANF in parabolic trough collectors (PTC), a promising collector for solar thermal systems. Design/methodology/approach A representative flow and heat transfer study of different fluids in a straight tube is conducted, and the basic energy equation and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…To the authors knowledge, the scientific literature dedicated to hybrid [152,153] and plasmonic [154] nanofluids is very scarce, preventing any conclusion concerning their potential in concentrating NDASC to be established. The influence of the volume fraction and fluid depth has been evaluated and similar conclusions are achieved: there is an optimum volume fraction and fluid depth for which the collector efficiency reaches a maximum value (Figure 9) [89,[155][156][157][158]. To our knowledge, the impact of the particle size and shape on the efficiency of concentrating NDASC has not been studied.…”
Section: Concentrating Ndascmentioning
confidence: 66%
See 1 more Smart Citation
“…To the authors knowledge, the scientific literature dedicated to hybrid [152,153] and plasmonic [154] nanofluids is very scarce, preventing any conclusion concerning their potential in concentrating NDASC to be established. The influence of the volume fraction and fluid depth has been evaluated and similar conclusions are achieved: there is an optimum volume fraction and fluid depth for which the collector efficiency reaches a maximum value (Figure 9) [89,[155][156][157][158]. To our knowledge, the impact of the particle size and shape on the efficiency of concentrating NDASC has not been studied.…”
Section: Concentrating Ndascmentioning
confidence: 66%
“…Several methods are commonly used to characterize the absorption properties of the nanofluid depending on the particle type, shape and mean size. The Rayleigh scattering approximation is the most accurate and popular solution method [1,12,26,31,32,[83][84][85][86][87][88][89][90][91][92][93][94], other methods such as the Mie scattering theory [92,[95][96][97] or the Maxwell-Garnett theory being less used [91,98]. Among metal nanoparticles, gold (Au), silver (Ag), copper (Cu), and aluminum (Al) show the best optical properties for NDASC.…”
Section: Physical Principles and Properties Of Nanofluidsmentioning
confidence: 99%
“…The other is to further improve the thermal performance of evacuated tubes. Researchers have studied different aspects in this regard (Bellos et al, 2019;Kasaeian et al, 2020;Nkwetta et al, 2012;Shariatifard et al, 2022;Yang et al, 2015). Teles et al (2019) focused on the effect of a solar tracking system on the performance of the evacuated tube solar collector.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the cylinder with a 30 mm diameter is the best choice to improve thermal efficiency. Moreover, the thermal enhancement is found to be greater at higher temperature levels and can reach up to 1% for an inlet temperature of 650 K. Kasaeian et al (2019) evaluated the influence of MWCNT/ethylene glycol (EG) nanofluid for the application of a parabolic trough collector. They focused on the impact of direct absorption nanofluid in parabolic trough collector which is a new generation of solar collector.…”
Section: Introductionmentioning
confidence: 99%